2018
DOI: 10.1016/j.ergon.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Change detection support for supervisory controllers of highly automated systems: Effects on performance, mental workload, and recovery of situation awareness following interruptions

Abstract: a b s t r a c tDynamic Positioning (DP) is a computer-controlled process to automatically keep a floating vessel at a specific position or to follow a pre-defined path (tracking) by using its own propellers and thrusters. The human supervisory controller has no direct need to constantly know what the status is of all parts of the automation and the system it is controlling, because the highly automated DPS is controlling all components itself. Only after a failure arises, the operator needs to take over manual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Several operators indicated that they would prefer more elaborate forms of prognosis information and information about alternative routes. However, previous research also indicates that complex change detection for SA support can result in higher operator workload (van der Kleij et al 2018). It, therefore, is questionable whether more elaborated context-dependent information visualization would result in even better support for operators' SA, workload, and task performance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several operators indicated that they would prefer more elaborate forms of prognosis information and information about alternative routes. However, previous research also indicates that complex change detection for SA support can result in higher operator workload (van der Kleij et al 2018). It, therefore, is questionable whether more elaborated context-dependent information visualization would result in even better support for operators' SA, workload, and task performance.…”
Section: Discussionmentioning
confidence: 97%
“…In case of our study, this could have explained our findings if the workload of operators' working with a coherent UI was all right, while the workload with the other two UI was either too high or too low. Adding support to an already highly automated system should be done with caution as under continuous, non-interrupted conditions, the change detection for SA support can result in higher operator workload (van der Kleij et al 2018). Since no significant difference in workload was found, this apparently was not the case.…”
Section: Discussionmentioning
confidence: 99%
“…Employees who receive more emotional instrumental support from their work supervisors in coping with life and family concerns can less prone to experience job interfering with their personal lives and causing them to feel burdened, even when the workload is high [2,58]. Workers perceive supervisory support as an indication that their bosses care about their happiness and their needs, thus decreasing the resource depletion caused by work-family conflict and job demands (workload) [59].…”
Section: Supervisor Work-life Support and Workloadmentioning
confidence: 99%
“…Typical solutions involve presenting users with an event timeline or log of changes (Hodgetts et al, 2015), an “instant replay” of events (e.g., St. John et al, 2005), or an indicator next to the changed values (van der Kleij et al, 2018) to support operators in their resumption of the primary task after an interruption. The theoretical underpinning for such tools is the Memory for Goals theory (MfG; Altmann & Trafton, 2002), which suggests that goal activation levels decay with time, with the current goal having the highest activation level.…”
Section: Introductionmentioning
confidence: 99%